PEMBENTUKAN KALUS REMAH DARI EKSPLAN DAUN RAMIN (Gonystylus bancanus (Miq) Kurz.) - nfn Yelnititis (Jurnal Pemuliaan Tanaman Hutan, 2012)
Ramin (Gonystylus bancanus (Miq.) Kurz) is the most favourite and the most over exploited woody species. This species has been listed in CITES APPENDIX II from 2004. The purpose of this experiment is to obtain the best treatment for friable and embryogenic callus formation that can develop to somatic embryo. Basal Murashige and Skoog (MS) media was used as growth medium. The experiment was conducted in three stages : callus induction and propagation stage, friable callus induction stage and embryogenic callus induction stage. The treatment of 3.0 – 5.0 mg/l 2,4-D was used for callus induction. The best of callus was propagated in 5.0 mg/l 2,4-D + 1.0 – 2.0 mg/l thidiazuron. The best of callus was subcultured for callus friable induction used 6.0 mg/l 2,4-D + 1.0 – 2.0 mg/l thidiazuron + 1.0 – 2.0 mg/l biotin. The best friable callus was subcultured for embryogenic callus induction used 7.0 – 8.0 mg/l 2,4-D + 1.0 – 2.0 mg/l biotin. The observation was made on texture, percentages, performance and color of friable callus. The results showed that callus can be induced on 5.0 mg/l 2,4-D. The treatment of 6.0 mg/l 2,4-D + thidiazuron produced friable callus yellowish on color. 2,4-D + biotin treatment produced very friable callus with yellowish on color and with no embryogenic callus development.